Willensstörungen in der Psychopathologie - Fuchs, Thomas; Broschmann, Daniel (Der Nervenarzt, 2017)
At the beginning of modern psychopathology the notion of the will had a high significance. Thus, the works of Eugen Bleuler, Emil Krapelin and Karl Jaspers show an intensive study of disorders of the will, such as abulia, ambivalence or disorders of impulse control. Retrospectively, changes of the scientific paradigms in psychology could be one of the reasons for a break, which led to giving up the concept of the will in psychopathology. With increasing interest in issues of agency and free will, however, a reactivation of this central concept could close a gap in psychopathology as well as in therapeutic practice. Methodologically, a psychopathology of the will may be founded on a differential typological phenomenology. To this purpose, the article first proposes a classification along the structural components of conation, suspension and volition, then gives a temporal analysis of the predecisional, the decisional and the postdecisional phases. The aim of the article is to help identify different disorders of the will, thus also furthering a psychotherapy of will, which can be connected with both cognitive behavioral and psychodynamic approaches.